Melindungi Generasi Muda: Penegakan Hukum Terhadap Narkotika Anak - Rahma Rahma; Muh. Natsir; Muh. Tahir (Jurnal Litigasi Amsir, 2024)
This research aims to examine the considerations of judges in imposing sanctions on drug cases involving minors in group I (Decision Study Number 42/Pid.Sus.Anak/2022/PN.Mks) and the solutions for handling drug cases involving minors in the city of Makassar. This research employs a normative legal research method focusing on positive law, legal principles and doctrines, legal discovery in cases, legal systematics, comparative law, and legal history. The findings reveal that the judges' considerations in imposing sanctions based on Decision Number 42/Pid.Sus.Anak/2022/PN.Mks involve witness statements, available evidence, juridical facts, and indictments from the public prosecutor, with the primary consideration being the defendant's minor status. Efforts to address drug cases involving minors in Makassar include establishing a national narcotics agency, enacting specific narcotics legislation, and providing drug counseling and rehabilitation for children involved in or exposed to drug abuse.